Health workers' social networks and their influence in the adoption of strategies to address the stillbirth burden at a subnational level health system in Uganda - Eric Ssegujja; Isaac Ddumba; Michelle Andipatin (Public Library of Science (PLoS), 2022)
Health workers' peer networks are known to influence members' behaviours and practices while translating policies into service delivery. However, little remains known about the extent to which this remains true within interventions aimed at addressing the stillbirth burden in low-resource settings like Uganda. The objective of this study was to examine the health workers' social networks and their influence on the adoption of strategies to address the stillbirth burden at a subnational level health system in Uganda. A qualitative exploratory design was adopted on a purposively selected sample of 16 key informants. The study was conducted in Mukono district among sub-national health systems, managers, health facility in-charges, and frontline health workers. Data was collected using semi-structured interview guides in a face-to-face interview with respondents. The analysis adopted a thematic approach utilising Atlas. ti software for data management. Participants acknowledged that workplace social networks were influential during the implementation of policies to address stillbirth. The influence exerted was in form of linkage with other services, caution, and advice regarding strict adherence to policy recommendations perhaps reflective of the level of trust in providers' ability to adhere to policy provisions. At the district health management level and among non-state actors, support in perceived areas of weak performance in policy implementation was observed. In addition, timely initiation of contact and subsequent referral was another aspect where health workers exerted influence while translating policies to address the stillbirth burden. While the level of support from among network peers was observed to influence health workers' adoption and implementation of strategies to address the stillbirth burden, different mechanisms triggered subsequent response and level of adherence to recommended policy aspects. Drawing from the elicited responses, we infer that health workers' social networks influence the direction and extent of success in policy implementation to address the stillbirth burden at the subnational level.